Membangun Kesadaran Gizi Seimbang: Upaya Pencegahan Stunting Melalui Sosialisasi di Desa Muncung - Devi Ayu Kurniawati; Nazwa Sabrina Fatihah; Sri Damayanti; Muhamad Zaidan Numan Hakim; Ayu Novianti; Apriyani Apriyani (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This community service activity highlights the serious issue of stunting in Indonesia, specifically in Muncung Village, Kronjo District, Tangerang Regency, Banten. The program aims to raise public awareness about the importance of balanced nutrition in preventing stunting. The method used involves a series of steps: planning, preparation, and implementation. The outreach event held on July 22, 2024, engaged 30 participants from the village and 7 students from the Community Service Program (KKM) of Universitas Bina Bangsa. The results indicated an increased understanding among participants of the critical role of nutrition in child development, especially during the first two years of life. The community became more aware of how to select and prepare nutritious foods readily available in their environment. This outreach is expected to promote healthy eating habits and support optimal child growth.